Integration of religious thought and student learning ethos in the covid-19 pandemic - Effendi, Muhamad Ridwan; Aulia, Rihlah Nur; Darma, Surya Hadi; Syahrezi, Rahviqi (ATTARBIYAH: Journal of Islamic Culture and Education, 2021)
This study discusses religious thoughts that affect the learning ethos of students during the Covid-19 pandemic, which has formed a new culture in the learning process that is carried out online (on the network). This study uses a qualitative method with data collection techniques in observation, interviews and literature review. In contrast, the data analysis method used is an analysis of the religious ideas of Jabariyah, Qadariyah, Ahlu Sunnah Waljama'ah in the indicators of a predetermined learning ethos. This research has shown the results that: first, the level of religious understanding of students has shown a significant influence on learning ethos during the covid-19 pandemic, second, there is a change in the learning ethic of students seen from indicators/moral aspects (attitudes, behaviour, habits). Al-Jiddu (resistance/persistence, sincerity), al-Thariiq (method), AlHimmah (interests, ideals), and al-Shobru (patience). Third, the flow of Ahlu Sunnah Waljama'ah thought in the socio-cultural environment of the Purwakarta community also contributed to strengthening religious literacy during the covid-19 pandemic. Thus, the influence of religious thinking on the learning ethos of students has implications for the intellectual repertoire in the theological and social fields and will shape academic attitudes and culture in their participation in strengthening community religious literacy